Reaction and Mass Transport Simulation of 3-Dimensional All-Solid-State Lithium-Ion Batteries for the Optimum Structural Design. (9th September 2015) - Itoh, Fumiya; Inoue, Gen; Kawase, Motoaki
Abstract : In order to increase energy density and enhance safety, all-solid-state lithium-ion battery has been developed as a storage battery for electric vehicles. However, its power density is too low to be applied for EV. In recent years, 3-dimensional electrode such as an interdigitated electrode is proposed, which can increase both energy density and power density. In this study, electrochemical reactions and mass transport phenomena of 3D all-solid-state battery were simulated with a porous electrode theory. Discharge property was improved by complicating 3D structures and Str. 2 displayed excellent discharge property at a rate of 1 to 10C and a solid electrolytes ionic conductivity of 0.01 to 1 S/m. Furthermore, the structure of which diffusion length is shorter than 36.57 μm can realize the full charge within 6 minutes at more than 1 S/m, and the diffusion length within 8 μm is necessary at 0.01 S/m to 1 S/m.